2002
DOI: 10.1046/j.1440-1819.2002.00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical overactivation in untreated schizophrenic patients: A functional magnetic resonance image finger‐tapping study

Abstract: Functional magnetic resonance imaging (fMRI) is a well established, non-invasive technique for mapping the working brain. Yet imaging of subcortical regions has proven to be difficult. We studied 40 subjects performing an unilateral self-paced finger-tapping task. Patients with schizophrenia according to DSM-IV treated with olanzapine (n = 10) or haloperidol (n = 10) were compared to healthy controls (n = 10) and untreated patients (n = 10). Brainvoyager software was used for data-analyzing. All subjects showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 41 publications
(97 reference statements)
4
40
0
Order By: Relevance
“…16 FMRI studies on motor activation in patients with schizophrenia also revealed decreased activation of the SMA. [17][18][19] Thus, reduction in SMA activity during motor tasks seems to be a common characteristic in PD and schizophrenia. Reduced SMA activity could be caused by a disturbed functioning either of the corticocortical circuit via the basal ganglia and the thalamus or of the cortico-cerebellar-thalamic-cortical circuit (CCTCC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 FMRI studies on motor activation in patients with schizophrenia also revealed decreased activation of the SMA. [17][18][19] Thus, reduction in SMA activity during motor tasks seems to be a common characteristic in PD and schizophrenia. Reduced SMA activity could be caused by a disturbed functioning either of the corticocortical circuit via the basal ganglia and the thalamus or of the cortico-cerebellar-thalamic-cortical circuit (CCTCC).…”
Section: Discussionmentioning
confidence: 99%
“…In the group treated with conventional antipsychotics, 10 patients received haloperidol (mean dose, 6.7 ± 3.5 mg/day standard deviation; range, 2-15) and four received fluphenazine (mean dose, 13.0 ± 6.78 mg/day; range, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The mean olanzapine dose was 17.7 ± 5.7 mg/day and the range was 10-30.…”
Section: Subjectsmentioning
confidence: 99%
“…For example Muller et al used a finger tapping task for an fMR study in which subjects had to tap in time to a specific pace (66). Volkow et al used PET to examine cerebellar metabolism in schizophrenia and observed reductions in both relative and absolute metabolic rates (67).…”
Section: Evidence For Cerebellar Abnormalities In Schizophreniamentioning
confidence: 99%
“…For example, lesions involving the caudate nucleus, putamen, globus pallidus, subthalamic nucleus, thalamus, and cerebellum have been associated with particular spontaneous dyskinesias in several studies using a variety of methodological techniques (e.g., Antonini et al, 1998;Dooling & Adams, 1975;Kim et al, 2002;Krystkowiak et al, 2000;Krystkowiak et al, 1998;LeDoux & Brady, 2003;Lehericy et al, 1996;Lenz et al, 2002;Lozza et al, 2002;Naumann et al, 1996;Perlmutter et al, 1997). Moreover, an array of structural and functional abnormalities have been observed in several of these regions in individuals with schizophrenia, although substantial variation in findings exists (e.g., Danos et al, 2002;Gunduz et al, 2002;Jernigan et al, 1991;Keshavan et al, 1998;Lang et al, 2001;Marcelis et al, 2003;McCreadie et al, 2002;Menon et al, 2001;Muller et al, 2002;Sigmundsson et al, 2001;Staal et al, 2000;Staal et al, 2001;Young et al, 2000). Thus, to the extent that it has been demonstrated in individuals with spontaneous dyskinesia and in individuals with schizophrenia, the presence of pathology in brain regions integral to normal movement control is consistent with a connection between movement abnormalities and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%